A Straight Deal; Or, The Ancient Grudge - Wister, Owen, 1860-1938 (Salt Lake City, UT : Project Gutenberg, 1998)
"A Straight Deal; Or, The Ancient Grudge" by Owen Wister is a non-fiction work likely written in the early 20th century. The book critically examines the historical grievances between the United States and England, particularly during and after World War I, while advocating for a more reconciliatory perspective on Anglo-American relations. Wister aims to address the lingering animosities and encourages readers to reassess their opinions on England, highlighting that such grudges can harm future cooperation and understanding. The opening portion of the text sets the stage for a discussion on how public sentiment and historical narratives shape perceptions of national identity and international alliances. Wister introduces the concept of a "letter box," likening the barrage of opinions on current events to falling leaves, suggesting that many are quick to voice opinions influenced by emotional responses rather than historical accuracy. He emphasizes the importance of personal experience and understanding in forming opinions about nations and their histories, particularly addressing anti-English sentiment that has roots in events like the American Revolution and the War of 1812. Through letters from soldiers and civilians alike, Wister begins to unpack these sentiments, indicating that a lack of accurate historical education may perpetuate these grudges, thus underlining the need for a more nuanced appreciation of England's contributions during critical moments in history. (This is an automatically generated summary.)
Release date is 1998-07-01
Produced by Bill Brewer, and David Widger
Keywords: United States -- Relations -- Great Britain; Great Britain -- Relations -- United States